The Issue of Delays in the Execution of Government Investment Projects in Iraq: An Applied Study in Light of The Implementation Instructions for Government Contracts No. 2 Of 2014 With A Comparison to the Jordanian Model - Atiyah, Roua’a (Journal of Legal Sciences, 2025)
The delayed execution of government investment projects is one of the most pressing challenges facing development in Iraq. Despite the existence of the Government Contracts Implementation Instructions No. 2 of 2014, these delays persist and often result in substantial economic losses and missed investment opportunities. This research aims to analyze the legal and administrative reasons behind the repeated delays in the implementation of such projects. It adopts a practical approach by examining selected case studies and official audit reports from Iraqi oversight bodies to identify the main weaknesses in the legal framework, particularly regarding the bidding process, contract awarding, execution phases, penalty mechanisms, and follow-up procedures. The delay in the completion of government investment projects in Iraq is a recurring and ongoing phenomenon that casts negative shadows on the developmental and economic reality. It has become a real barrier to improving the investment environment and attracting capital. The main reason for this delay is attributed to deficiencies in the legal and regulatory framework governing government contracts, especially the Government Contracts Execution Instructions No. (2) of 2014, which were not designed adequately to address emergencies and changes that occur during execution. The current mechanisms do not ensure speed in allocation, and they suffer from the multiplicity of oversight bodies and overlapping authorities, creating excessive bureaucracy. Furthermore, the study provides a comparative analysis with the Jordanian model, which has demonstrated relative success in improving the efficiency of public investment projects. By exploring the legal structure and regulatory practices in Jordan—especially the public procurement system and digital oversight tools—the study aims to extract valuable lessons that could inform Iraqi legal reforms.